2022
DOI: 10.1039/d1fo02857j
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene ameliorates atrazine-induced pyroptosis in spleen by suppressing the Ox-mtDNA/Nlrp3 inflammasome pathway

Abstract: Nlrp3 is a vital integration point of diverse extracellular stimuli and cellular stress. However, inappropriate activation of Nlrp3 results in progression of autoinflammatory and metabolic disorders. Atrazine, using widely in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 61 publications
(81 reference statements)
2
26
0
Order By: Relevance
“…This suggested that ATZ could induce inflammation in mice, which was consistent with the previous study. 4 The concentrations of TNF-α, IL-6 and IL-10 in both ATZ1 + L and ATZ2 + L were not different from the control group. It seemed that Lyc ameliorated ATZ-induced inflammation.…”
Section: Papermentioning
confidence: 80%
See 4 more Smart Citations
“…This suggested that ATZ could induce inflammation in mice, which was consistent with the previous study. 4 The concentrations of TNF-α, IL-6 and IL-10 in both ATZ1 + L and ATZ2 + L were not different from the control group. It seemed that Lyc ameliorated ATZ-induced inflammation.…”
Section: Papermentioning
confidence: 80%
“…ATZ can induce pyroptosis in splenocytes via the Ox-mtDNA/Nlrp3 inflammasome pathway. 4 Additionally, our previous study has provided evidence that ATZ also induced apoptosis in B cell zones by inhibiting the expression of Foxo1 (the data are not shown). The dysregulation of B cells contributes to immunodeficiency.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations